Pengaruh Strategi Problem Based Learning terhadap Perilaku Sosial Siswa Kelas V dalam Pembelajaran Akidah Akhlak di MIN 3 Labuhanbatu Selatan - Rizki Hafni Rambe; Afrahul Fadhila Daulai; Zulfiana Herni (Moral : Jurnal kajian Pendidikan Islam, 2024)
This study aims to determine the influence of the Problem Based Learning strategy on the social behavior of fifth grade students in learning Akidah Akhlak at MIN 3 South Labuhanbatu. To discuss and examine the problems described above, the author uses quantitative data management, the author determines a sample of 2 classes as experimental and control classes, namely 32 students in class V-A as the experimental class, and 32 students in class V-B as the control class. This was done to find out how the influence of the Problem Based Learning strategy on the social behavior of fifth grade students in learning Akidah Akhlak at MIN 3 South Labuhanbatu. The research hypothesis testing used regression analysis. The results of the regression calculation showed a regression equation of 48.615 0.353X and a correlation coefficient of R value of 0.862 which if interpreted based on the table can be interpreted as the relationship between the two variables, namely the Problem Based Learning learning strategy (X) with the social behavior variable in learning Akidah Akhlak (Y) in the very strong category and the hypothesis can be accepted.